Dynamic Behavior of Satellite and Its Solar Arrays Subject to Large-Scale Antenna Deployment Shock - Zhang, Jie; Wu, Pengfei; Han, Qinghu; Wei, Xin; Duan, Yi (Aerospace, 2024)
Satellites should be equipped with more and more deployable, large, flexible appendages to improve their service efficiency and reduce launch costs. The spring-driven deployment method of flexible appendages has been widely applied and generates great instantaneous shock loads on satellites, maybe affecting the safety of other flexible appendages, but the current related investigations for satellites with multiple large flexible appendages are insufficient. In this study, the deployment test of the antenna itself was conducted, and the attitude changes in a satellite during antenna deployment were telemetered. Then, a related dynamical model of the satellite was established and verified by the telemetry values of the satellite. Finally, the shock mechanism transmitted to solar arrays was analyzed, and the effect of solar array attitude was discussed. The results show that the simulated method of antenna deployment equivalent to the shock loads tested was thought to be efficient, though it could cause a small non-zero constant of the simulated angular velocities in the antenna deployment direction. The shock-induced moments, except the rotation direction of the solar array drive assembly (SADA), should be highlighted for the antenna deployment dynamic design of satellites, and the solar array attitude has few effects on the shock-induced loads at the SADA.